Cultural values in organisations: insights for Europe. (26th July 2007) - Sagiv, Lilach; Schwartz, Shalom H.
With the emergence of multicultural workplaces, understanding the impact of national culture on organisations is essential. This paper examines how the values of the society in which an organisation is nested affect the values of the organisation. We discuss three sources of influence: the value culture in the surrounding society, the personal value priorities of organisational members, and the nature of the organisation's primary tasks. We suggest that the societal culture influences organisational values directly and also indirectly through its impact on members' values and on the nature of organisational tasks. Implications for global management in European organisations are discussed.